49.9k views
0 votes
Match each expression in the left column with the correct product in the right column.

Options 6, -6, 6i, -6i

Match each expression in the left column with the correct product in the right column-example-1
User Bhantol
by
6.1k points

1 Answer

3 votes

Answer:

-6

-6i

6i

6

Explanation:

1) √4 . √-3 . √-3


$ √(4) = 2 $


$ √(-3) . √(-3) = (√(-3))^2 $


$ √(4) . (√(-3))^2 = 2 * -3 = $ -6

2) √-4 . √-3 . √-3


$ √(-4) = 2i $ .

Therefore,
$ √(-4) . √(-3) . √(-3) = 2. √(-1)  * -3 = 2i * (-3) =  $ - 6i

3) √4 . √3 . √-3


$ √(4) = 2 $


$ √(3) . √(-3) = (√(3))^2 . √(-1) $


$ \implies 2 * 3i = $ 6i

4) √4 . √3 . √3


$ √(4) = 2 $


$ √(3) . √(3) = (√(3))^2  = 3 $

Therefore, √4 . √3 . √3 = 2 . 3 = 6

User Demobilizer
by
5.5k points